The Impact of COVID-19 on Australian Higher Education - Leask , Betty; Ziguras, Chris (International Higher Education, 2020)
With international students comprising over a quarter of its student population, Australia is vulnerable to global shocks. The initial impact of COVID-19 was to prevent thousands of Chinese students from traveling to Australia for the new academic year. The unfolding lockdown, a shift to online teaching, and collapse of part-time work are affecting international students deeply. However, universities have transitioned to online operations quite seamlessly, which might bring lasting cultural change to their operations.